The adversarial principle, the evolution and current shape of civil procedure – outline of subject matter - Marciniak, Sławomir (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The adversarial principle has a long tradition in Polish civil procedure. It was one of the main principles under the Polish Civil Procedure Code of 1930. Later on, the change of the state system to socialism brought significant modifications to the shape of the subject principle. Due to the different bases of socialist civil procedure, the adversarial principle was almost completely forgotten. It was later resurrected, with another change of state system. The contemporary lawmaker is much interested in shaping the adversarial principle in the right way. The latest amendments to the Polish Civil Procedure Code of 1964 were focused on creating the proper bases for the functioning of the courts and for proper regulations regarding parties remaining active throughout the process. The presented analysis leads to the conclusion that the adversarial principle is, and always has been, of very high importance to civil procedure.